Companies and autonomous taxation in corporate income tax in Portugal - Rodrigues, Carlos (2023)
Since 1990 in Portugal, in addition to paying income tax, companies are also taxed for having incurred certain expenses, even though these expenses may be considered tax costs for the purposes of income tax. That is, even if those companies have tax losses and therefore do not pay any "income tax" for the simple fact of not having obtained it, even so, if they have recorded certain types of expenses, they will be taxed autonomously for having incurred those expenses. In our opinion, we are facing two concrete realities regarding this type of expenses subject to autonomous taxation, namely: Firstly, we are facing a tax on expenses; Secondly, the rules that tax these expenses are anti-abuse rules. In our study we will make a theoretical and practical analysis of this type of taxation, focusing on the legal rules and statistics. Finally, we intend to demonstrate the weight that at the end of each tax year the revenues obtained have in relation to the “income tax” actually paid by companies.